2018
DOI: 10.3390/min8070294
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sodium Ions, Phosphorus, and Silicon on the Eco-Friendly Process of Vanadium Precipitation by Hydrothermal Hydrogen Reduction

Abstract: The effects of sodium ions, phosphorus, and silicon on the eco-friendly process of vanadium precipitation by hydrothermal hydrogen reduction were investigated to establish the suitable concentrated solution system for this eco-friendly process. The results showed that sodium ions had no negative effects on the vanadium precipitation process. Phosphorus can reduce vanadate ion activity, and results in the decrease of vanadium precipitation percentage from 99.5% to 61.3%, as the phosphorus concentration in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…where A 11 , A 22 and A 33 are the Hamaker constants of MoS 2 , Mg(OH) 2 and water, respectively. The Hamaker constants of MoS 2 (A 11 ) and Mg(OH) 2 particles (A 22 ) are 9.38 Â 10 À20 J and 1.62 Â 10 À20 J, 29,30 respectively. The Hamaker constant of water A 33 is 3.7 Â 10 À20 J.…”
Section: Edlvo Calculationmentioning
confidence: 99%
“…where A 11 , A 22 and A 33 are the Hamaker constants of MoS 2 , Mg(OH) 2 and water, respectively. The Hamaker constants of MoS 2 (A 11 ) and Mg(OH) 2 particles (A 22 ) are 9.38 Â 10 À20 J and 1.62 Â 10 À20 J, 29,30 respectively. The Hamaker constant of water A 33 is 3.7 Â 10 À20 J.…”
Section: Edlvo Calculationmentioning
confidence: 99%
“…To date, the basic recovery technology for vanadium has been sodium-roasting leaching technology, which was first proposed by Birck in 1912 and is widely used in the Chinese industries since the 1980s [12][13][14]. The vanadium-containing ores are mixed with the sodium salts (sodium carbonate (800-1000 • C), sodium sulfate (1200-1250 • C), sodium chloride (750-850 • C), and sodium hydroxide (400-800 • C)) at determined mole ratios and then roasted in a vertical kiln under a high temperature atmosphere with O 2 [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to prepare pure-phase NaV2O5 through the HHR method by controlling reaction conditions. If so, the synthesis process can be low-cost, because In previous research, a vanadium precipitation process of hydrothermal hydrogen reduction (HHR) for synthesizing V 2 O 3 from ASPVS was first developed [27,28]. In the research, it was found that V(V) ions in the solution could be reduced to trivalent vanadium (V(III)) compounds or tetravalent vanadium (V(IV)) compounds by hydrogen (H 2 ).…”
Section: Introductionmentioning
confidence: 99%